2006
DOI: 10.1021/ja0549998
|View full text |Cite
|
Sign up to set email alerts
|

Potential Energy Landscape of the Photoinduced Multiple Proton-Transfer Process in the Green Fluorescent Protein:  Classical Molecular Dynamics and Multiconfigurational Electronic Structure Calculations

Abstract: The green fluorescent protein proton wire operating upon photoexcitation of the internally caged chromophore is investigated by means of classical molecular dynamics and multiconfigurational electronic structure calculations. The structure of the proton wire is studied for the solvated protein, showing that the wire is likely to be found in a configuration ready to operate as soon as the chromophore is photoexcited, and leading to a total of three proton translocations in the vicinity of the chromophore. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
125
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(137 citation statements)
references
References 44 publications
11
125
1
Order By: Relevance
“…In contrast to the single ESIPT process present in HBX, SA, and other related systems, GFP-like systems may undergo two or more ESIPT processes. [17,18] This opens the door to several reaction paths so that the possibility of obtaining a stable structure upon photoexcitation at a given wavelength largely increases. In fact, a GFP-like fluorescent protein called Dronpa has recently been proposed as a very promising candidate for a molecular photomemory.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the single ESIPT process present in HBX, SA, and other related systems, GFP-like systems may undergo two or more ESIPT processes. [17,18] This opens the door to several reaction paths so that the possibility of obtaining a stable structure upon photoexcitation at a given wavelength largely increases. In fact, a GFP-like fluorescent protein called Dronpa has recently been proposed as a very promising candidate for a molecular photomemory.…”
Section: Introductionmentioning
confidence: 99%
“…In GFP, an anionic and a neutral chromophore protonation state are interconverted through a proton-relay mechanism. [16][17][18][19][20] As protons are not observed in the X-ray crystal structures, their role and possible transfers during the kindling of asFP595 remain largely unclear.…”
mentioning
confidence: 99%
“…This situation is similar to that in GFP, where the neutral protonation state is also favored for the cis chromophore. [16][17][18][19][20] GFP fluorescence originates from the anionic chromophore, which is formed through excited-state proton transfer (ESPT). Further studies are required to elucidate whether such ESPT processes play an important role in asFP595 as well.…”
mentioning
confidence: 99%
“…15 All the three protons were placed at 1.0 Å from either the donor or the acceptor O atoms and the heavy atoms in the proton chain were restricted during calculations. A reasonable argument was reported that why complete relaxation of heavy atom may not be meaningful on the ESPT time scale.…”
Section: Proton Transfer In H-bonded Green Fluorescent Protein Modelmentioning
confidence: 99%
“…However, in their simulation the first proton transfer from chromophore to water was enforced excluding a fully concerted mechanism (The H1 was shifted to chromophore and the back transfer was forbidden, then simulation was started). Vendrell et al 15 reported that it is a rough concerted process by the treatment of freezing heavy atoms in the proton wires. As well, it was pointed out that the starting point of the ESPT process is the Ser25 proton transfer to Glu222, rather than the phenolic proton of chromophore, and the GSPT should take place via the same order.…”
Section: Introductionmentioning
confidence: 99%